Monitoring and Control System for Electrical Energy Consumption Based on The Internet of Things - Andi Syofian; Yugerita Firmance; Yultrisna Yultrisna (JECCOM: International Journal of Electronics Engineering and Applied Science, 2023)
Electrical energy consumption in the household sector is frequently uncontrolled, particularly when electronic devices are used. That is the tendency of users to forget to turn off or unplug the electronic device from the socket. In that case, modifications are made to the socket so that it can be controlled remotely via a smartphone. The hardware design uses the NodeMCU ESP8266 as a microcontroller combined with the PZEM-004T sensor module for electrical magnitude. Relay modules are used to secure the circuit in cases of higher loads. So that in the system, all three sockets can be monitored simultaneously. While the software design uses MIT App Inventor and Thingspeak Platform as servers. The data is saved in CSV format, which can be converted to Google Sheets or Microsoft Excel. Data is stored in the form of the name of the electronic equipment, the time of use, as well as voltage, current, power, cos phi, and electrical energy used. So that users can regulate the use of electrical equipment at home and reduce the waste of electrical energy. The test results showed the average faults for voltage, current, power, cos phi, and energy were 0.06%, 5.32%, 5.67%, 0.7%, and 7%, respectively.